Dizziness at a Canadian tertiary care hospital: a cost-of-illness study - Andre Le; Daniel A. Lelli; Sasha Van Katwyk; Debora Hogan; Kednapa Thavorn; Darren Tse (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background In the Canadian health care system, determining overall costs associated with a particular diagnostic subgroup of patients, in this case dizzy patients, is the first step in the process of determining where costs could be saved without compromising patient care. This study is the first Canadian study that evaluates these costs at a tertiary care hospital and will allow for the extrapolation of cost data for other similar academic health science centers, regional health initiatives, and provincial healthcare planning structures. Methods We conducted a retrospective cohort study of patients of any age presenting to The Ottawa Hospital (TOH), a tertiary care hospital, between January 1st, 2009 and December 31st, 2014 with a main diagnosis of dizziness or dizziness-related disease. De-identified patient information was acquired through TOH Data Warehouse and included a patient’s sex, age, arrival and departure dates, Elixhauser co-morbidity score, location of presentation (emergency department or admitted inpatient) presenting complaint, final diagnosis code, any procedure codes linked to their care, and the direct and indirect hospital costs linked with any admission. We derived the mean hospital costs and 95% confidence interval for each diagnosis. We obtained the number of patients who were diagnosed with dizziness within Ontario in year 2015–16 from Canadian Institute for Health Information (CIHI). A simple frequency multiplication was performed to estimate the total cost burden for Ontario based on the cost estimate for the same year obtained from TOH. Cost data were presented in 2017 Canadian dollars. Results The average total hospital cost per patient with dizziness for the entire cohort is $450 (SD = $1334), with ED only patients costing $359 (SD = $214). The total estimated hospital cost burden of dizziness in Ontario is $31,202,000 (95% CI $29,559,000 – 32,844,000). Conclusions The estimated annual costs of emergency department ambulatory and inpatient dizziness in Ontario was calculated to be approximately 31 million dollars per year. This is the first step in identifying potential areas for cost savings to aid local and provincial policy-makers in allocation of health care spending.